Krisis Citra Merek dan Perbedaan Manajemen Lintas Budaya pada Fenomena Boikot McDonald's di Konflik Israel - Palestina - Alzetrho Baja Pratama; Nouval Dwi Wicaksono; Adytrio Reyhan Sudrajat (Universitas 45 Surabaya, 2026)
The geopolitical conflict between Israel and Palestine has triggered a wave of global solidarity, including boycott movements against multinational brands like McDonald's, which are perceived to support one side. This study aims to analyze the impact of geopolitically triggered boycotts on brand image decline in Muslim-majority markets, while evaluating the role of franchise structures and local management autonomy in creating cross-cultural crisis communication challenges. This research employs a comparative case study approach, comparing McDonald's responses in Israel, Malaysia, and Indonesia based on secondary data from online news, official statements, and research reports. The findings indicate that the unilateral actions of McDonald's Israel in providing logistical support to the military directly triggered negative consumer perceptions in Indonesia and Malaysia, despite local franchises' clarification efforts and humanitarian aid. The inconsistency in responses across franchises demonstrates a failure of cross-cultural management within a decentralized structure, where the actions of a single local unit can collapse global brand equity and validate public support for the Boycott, Divestment, and Sanctions (BDS) movement. The implications of this study suggest that multinational companies should implement centralized crisis communication protocols that establish strict ethical boundaries regarding geopolitical conflicts to maintain global brand image consistency over local operational autonomy.